TOURISM, TOURISTS AND SOCIETY (Web of Technology: Multidimensional Research Journal, 2024)
Tourism is a rapidly growing industry that has significant impacts on both the destination and the tourists. Tourists often bring economic benefits to the areas they visit, but their presence can also have negative effects on the environment, culture, and infrastructure of the destination. This article explores the complex relationship between tourism, tourists, and society, and examines the various ways in which tourism can influence and be influenced by the societies in which it occurs.